1998
DOI: 10.4269/ajtmh.1998.59.628
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in Indonesia: a hospital-based study and a community-based survey.

Abstract: Abstract. Hospital-based and community-based studies were conducted to understand the prevalence and mode of transmission of Cryptosporidium parvum infection in Surabaya, Indonesia. In both studies people with and without diarrhea were examined for oocysts. A community-based survey included questionnaires to a community and stool examination of cats. Questionnaires covered demographic information, health status, and hygienic indicators. In the hospital, C. parvum oocysts were found in 26 (2.8%) of 917 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 25 publications
3
35
0
3
Order By: Relevance
“…3,6,8,10,29 Our study similarly found a significant association between the odds of C. parvum infection and the occurrence of rain (Figure 1). Similar trends were also observed in other regions of Brazil, and in Indonesia and Zambia.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…3,6,8,10,29 Our study similarly found a significant association between the odds of C. parvum infection and the occurrence of rain (Figure 1). Similar trends were also observed in other regions of Brazil, and in Indonesia and Zambia.…”
Section: Discussionsupporting
confidence: 66%
“…Similar trends were also observed in other regions of Brazil, and in Indonesia and Zambia. 3,6,10,29 The biologic source(s) for C. parvum infection and the exact routes of transmission during these wetter months have not been well described, but the impact of rainfall has been shown to mobilize and transport C. parvum oocysts out of fresh fecal material and fecal slurries and across vegetated soil surfaces and through soil columns. [30][31][32][33] Increased numbers of cases of C. parvum infection in Fortaleza and Lusaka during the rainy season were associated with contaminated drinking water supplied to these population, 3,6 but source of drinking water and mode of water disinfection were not associated with the odds of C. parvum infection among our study population.…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the crowded conditions in a household, which may translate into more frequent human-to-human contact, especially with children diarrhea, thus increasing the risk of Cryptosporidium transmission within families. [28][29][30] It was previously found that residents who raised livestock or poultry were more likely to be infected with Cryptosporidium in this area, supporting the hypothesis of zoonotic transmission of domestic animals. Domestic pigs in this region were mostly free ranging and tended to be around the residences.…”
Section: Discussionmentioning
confidence: 64%
“…In low-income countries, where the water supply and sanitation system and the causative agents of diarrhoea are likely to be different from those in high-income countries, post-flood increases in cholera (Sur et al 2000), rotavirus diarrhoea (Ahmed et al 1991;Fun et al 1991), cryptosporidiosis (Katsumata et al 1998) and non-specific diarrhoea (Woodruff et al 1990;Siddique et al 1991;Biswas et al 1999;Mondal et al 2001;Kondo et al 2002;Kunii et al 2002) have been reported. Most of these studies had methodological limitations, in particular lack of pre-flood data, lack of comparison groups and potential recall bias.…”
mentioning
confidence: 99%